The repatriation of Greek prisoners of war from the Turkish military camps of Asia Minor (April 1923 – April 1924) - Nikos Tompros; Nikos Kanellopoulos (Nuova Antologia Militare)
The aspirations of the Megali Idea, nurtured by generations of Greeks, were permanently put to rest in Lausanne with the signing, by Greece and Turkey, of the homonymous Peace Treaty (24 July 1923). Almost six months earlier (17/30 January 1923), in the same Swiss city, the two states had co-signed diplomatic acts (Agreements and Protocols) for the mutual exchange of populations and prisoners of war. In contravention to what was stipulated in the relevant agreements, the repatriation of Greek prisoners of war took place in stages, over a period of thirteen months. The bulk of the POWs, however, arrived in Greece in April and August 1923. Scholarly interest in the repatriation of these prisoners is manifold. First and foremost, it addresses a gap in Greek historiography relating both to their numbers and the conditions under which they arrived in Greece. Knowing the total number of returning soldiers, coupled with the number of those captured by Kemal’s forces in the period 1919–1922, allows one to calculate the extent of human losses suffered by the Greek soldiers during their captivity. Further, the image of the repatriates may act as irrefutable evidence of the billeting conditions in Asia Minor, leading to certain safe remarks regarding their detention in Turkish concentration camps. Focusing on the quantification of Greek prisoners, thus, what follows is an attempt at documenting their “journey” from Turkey to Greece, the public discourse that developed around them, as well as any effort at instrumentalizing them undertaken both by the Turkish and Greek sides respectively.